Implementación por primera vez de los estándares internacionales de información financiera IFRS 1 en Cooperativas de Ahorro y Crédito, caso Cofincafe, en el rubro de propiedades, planta y equipo, oficina de Tuluá (2012)
The document describes the importance of First-time Adoption of International Financial Reporting Standards (IFRS) in Cooperatives of Saving and Credit, bearing in minds that in the measure that they grow and expand in other territories, his financial information happens to be of the interest of new users in the international scene. To achieve it, it´s necessary to realize a process of recognition, measurement, presentation and revelation of the above mentioned information; in order to obtain one that is homogeneous, comparable and of easy interpretation, which allows to reach an authentic universal language of communication.